PERFOMANCE EVALUATION OF TWO IMPORTANT PROTOCOLS FOR INTER-NAVAL COMMUNICATION (AODV AND DSDV) WITH DARS SIMULATOR: A CASE STUDY OF THE SEAPORT OF VLORA - Hoxha, Esmeralda (European Scientific Journal, ESJ, 2015)
The aim of this paper is to use simulations to evaluate the performance of two existing protocols, AODV (ad hoc on-demand distance vector routing) and DSDV (Destination-sequenced Distance-Vector routing). However, they are designed for use in mobile ad hoc networks (MANET) and for increasing the effective point to point (ship to ship) communication. Simulations will be performed with the DARS simulator. The simulation result shows that when the number of nodes increased and consequently the distance between nodes narrows, there is an improvement in the communication process and a "Message Transmission Successful’. In fact, routing in these networks is based on a simple and intuitive approach. Thus, this approach shows that the retransmission of the packets by each node allows propagation through the network.